Amino acid supplementation to growing and finishing steers - C.G. Campbell; C.T. Milton; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1996)
One hundred British and British cross steers, averaging 631 lb ( initial wt) were used in a growing and finishing study to evaluate the effects of unprotected amino acid supplementation on cattle performance and carcass characteristics. All diets contained 1% of a nonprotein nitrogen source, and treatments were: no additional supplemental protein (UREA), 2) supplemental protein from soybean meal (SBM), 3) 13 grams/day of an amino acid supplement (Low AA), and 4) 26 grams/day of an amino acid supplement (High AA). The Low AA treatment supplied 2 grams methionine, 8 grams lysine, 2 grams threonine, and 1 gram tryptophan per day, whereas the High AA treatment provided twice those amounts. The grower diet was based on whole-plant sorghum silage, and the finishing diet was based on rolled corn and corn silage. During the growing period, gains were higher (P<.05) for SBM-supplemented steers than for UREA steers and intermediate for amino acid-supplemented steers. Intakes were higher for steers supplemented with Low AA than for those supplemented with UREA or High AA. Few significant differences among treatments were observed in cattle performance during the finishing period. Hot carcass weights, dressing percentage, KPH fat, and yield grade were unaffected by amino acid supplementation. In this study, supplementing growing and finishing cattle with unprotected amino acids did not significantly improve steer performance or carcass characteristics, suggesting either that these amino acids were not limiting in these steers or that not enough of these supplemented amino acids escaped ruminal degradation to affect steers' performance.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Amino acids; Steers; Feedlot; Performance